Maximinus Thrax, General of Severus Alexander or Victor over the Persians? Some Considerations Concerning the Sources of Quintus Aurelius Symmachus’ Roman History - Vitiello, Massimiliano (Histos, 2015)
This article explores the historiographical accounts that attest the presence of Maximinus Thrax in the Persian campaign of Severus Alexander. The Western tradition is silent about this episode, except for a brief passage in Jordanes' Getica. Jordanes acknowledges his source for Maximinus as the lost Roman History of Symmachus the Younger. Yet neither the remarkable designation of Severus Alexander as 'Alexander Mamaeae' nor Maximinus' Persian campaign under Severus Alexander appear in those works which modern scholars commonly understand to be the sources of Symmachus' information about Maximinus: that is, the Life of the Two Maximini in the Historia Augusta and Orosius. Further, while Herodian and some Byzantine historians shed some light on Maximinus' presence in Persia, none of these accounts appears to share a common source with the item from Symmachus' History. Thus Jordanes' reference to Maximinus in Persia reveals the presence of a Greek source used by Symmachus that was evidently a distinctive element in the extremely complex historiographical tradition surrounding Severus Alexander's Persian campaign. As an exercise in Quellenforschung, this article also sheds light on the compositional methods of all the historians discussed, above all Jordanes and Symmachus, the creativity and independence of both of whom continues to be a matter of considerable scholarly controversy.